(3eHQR GdbhGYO GdEYQGHjI ef GdbUjOI GdeLQGOjIs - (3Ydj Hf CMeO Hf eMeO GdQLQGLi GdLRhdi GdQSehcis; (3CHh YHO Gddg eMeO Hf eMeO Hf eMeO Hf YeQGf GdaRGQj GdSdGhj GdeLQGOj, GHf GdeLQGOj,J (B778 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje jbhd YHO Gddg JYGdi CSjQ PfHg GdQGLi Yah QHg hHYO adeG cGfJ bUjOI GdTjN GdEeGe YHO Gddg eMeO Hf eMeO Hf YeQGf GdTgjQ HGdeLQGOi ef CLd eG Cda ai bhGYO GdEYQGH SGdeI ai CdaGXgG ef GdEZQGH s
(3BNQgG (B:s
(3hJYGdi aYd eG Vi haGYdg VejQ eSJJQ ajg YGFO Ydi CNhg hGdLedI Udg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B286s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdfMhs